Vertically resolved chemical characteristics and sources of submicron aerosols measured on a Tall Tower in a suburban area near Denver, Colorado in winter. Issue 24 (18th December 2013) - Öztürk, F.; Bahreini, R.; Wagner, N. L.; Dubé, W. P.; Young, C. J.; Brown, S. S.; Brock, C. A.; Ulbrich, I. M.; Jimenez, J. L.; Cooper, O. R.; Middlebrook, A. M.
Abstract [1] The Nitrogen, Aerosol Composition, and Halogens on a Tall Tower study was conducted at the Boulder Atmospheric Observatory in Colorado during February–March 2011. A compact time‐of‐flight aerosol mass spectrometer was installed in a moving carriage on the tower, obtaining vertical profiles of submicron nonrefractory aerosol mass concentrations (<alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgg4sp9hjsm" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />PM1nr</alternatives>) from 0–265 m above ground level. The average <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgg4sp9hkj8" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />PM1nr</alternatives> was 4.6 ± 5.7 µg/m3, with average contributions of nitrate, organics, sulfate, ammonium, and chloride of 35%, 26%, 20%, 17%, and 1%, respectively. Positive Matrix Factorization analysis of the organic aerosol (OA) mass spectra indicated that average contributions of oxygenated organic aerosol (OOA)‐I, OOA‐II, and hydrocarbon‐like organic aerosol (surrogates for aged and fresh secondary OA and primary OA, respectively) to OA mass were 52%, 32%, and 16%, respectively. There was considerable variability in the vertical profiles of aerosol mass loading and composition, especially at the lowest heights. Below 40 m, the highest <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgg4sp9hkg5" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />PM1nr</alternatives> concentrations were composed of mostly nitrate (30–46%) and were associated with winds from the northeast where there are large agricultural facilities. When winds were southerly, <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgg4sp9hkpg" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />PM1nr</alternatives> mass distributions near the surface had small, fresh OA, indicating the influence of nearby Denver urban emissions at the site. The largest contribution to OA mass at these heights was OOA‐II (~43%). Between 40 and 120 m, trajectory cluster analysis indicated that during high‐altitude long‐range transport events, daytime aerosol composition was dominated by sulfate, whereas during low‐altitude transport events, the contributions of sulfate, nitrate, and OA were comparable. OOA‐I contributed the most (53–68%) to OA mass at these tower heights.